Limit Cycle, Gauge Field and Some Unifications in Particle Physics - Saiswathi; Kanth, Sudeepthi (The journal of contemporary issues in business and government, 2020)
The first step is to look for different limit cycles in particle physics. Following that, we look at the relationships between the limit cycle and the oscillation-wave, as well as the limit cycles in the gauge field and the dynamical model, and the gauge field and the qualitative analysis theory, among other things. In addition, we investigate the limit cycle as well as several unified theories on particles. In addition, the limit cycle is a specific string. It is possible to gain some new mathematical findings and equations. Last but not least, numerous scenarios for the limit cycle's future evolution are offered.